2012
DOI: 10.3389/fcimb.2012.00128
|View full text |Cite
|
Sign up to set email alerts
|

Diverse phosphorylation patterns of B cell receptor-associated signaling in naïve and memory human B cells revealed by phosphoflow, a powerful technique to study signaling at the single cell level

Abstract: Following interaction with cognate antigens, B cells undergo cell activation, proliferation, and differentiation. Ligation of the B cell receptor (BCR) leads to the phosphorylation of BCR-associated signaling proteins within minutes of antigen binding, a process with profound consequences for the fate of the cells and development of effector immunity. Phosphoflow allows a rapid evaluation of various signaling pathways in complex heterogenous cell subsets. This novel technique was used in combination with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…21 We found similar results in our antigen-experienced CD27 1 B cells also express IgM (44-49%) with no significant differences between patient phenotypes found ( Figure 4). …”
Section: B Cells From Patients With Cgvhd Have Increased Bcr-driven Ssupporting
confidence: 86%
See 1 more Smart Citation
“…21 We found similar results in our antigen-experienced CD27 1 B cells also express IgM (44-49%) with no significant differences between patient phenotypes found ( Figure 4). …”
Section: B Cells From Patients With Cgvhd Have Increased Bcr-driven Ssupporting
confidence: 86%
“…21 Intracellular staining was performed according to the manufacturer's instructions (BD Biosciences). Cells were fixed (BD cytofix buffer), permeabilized (BD Perm Buffer III), and stained using the following antibodies from BD Biosciences: BLNK (clone 2B11) or Syk (clone 4D10).…”
Section: Intracellular Flow Cytometrymentioning
confidence: 99%
“…Since it has been shown that naive and memory B cells have different BCR activation thresholds , further analyses were performed using conventional CD27− naive and CD27+ memory B cells. Of note, the recently published memory‐like CD27−Syk++ B cell subset was excluded from the CD27− naive B cell compartment and analyzed separately (Supplementary Figure , online at http://onlinelibrary.wiley.com/doi/10.1002/art.39559/abstract).…”
Section: Resultsmentioning
confidence: 99%
“…IgM + memory B cells express approximately twice as many BCRs on their surface than naïve B cells (Figure 5a). 12 , 13 , 26 , 55 To test the possibility that the significant differences in Ca 2+ mobilization between naïve B cells and IgM + memory B cells (Figures 3c) resulted from differences in the amounts of surface IgM, naïve and IgM + memory B cells were stimulated with different concentrations of F(ab’) 2 anti‐Igμ and Ca 2+ mobilization was then tracked. The level of Ca 2+ mobilization increased in a dose‐dependent manner in both naïve and IgM + memory B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have utilized immortalized B‐cell lines from different species, 4 , 31 , 39 primary B cells from transgenic mice 37 , 46 , 51 or syngeneic or heterologous overexpression systems 39 , 57 . More recently, some studies have addressed BCR signaling events in primary human B cells 40 , 47 , 55 . These have revealed the complexities of BCR signal transduction and documented the influence of the Ig isotype on these processes with respect to the kinetics and magnitude of the response 4 , 32 , 33 , 41 .…”
Section: Discussionmentioning
confidence: 99%